1988
DOI: 10.1007/bf00154342
|View full text |Cite
|
Sign up to set email alerts
|

Some vectorized random number generators for uniform, normal, and poisson distributions for CRAY X-MP

Abstract: It is amusing to note how the initial pessimism about vector/parallel methods for Monte Carlo simulations has now been replaced with requests for better and faster vcctorizcd random number generators for those purposes. In fact, much of the impetus for establishing the NSF supercomputer centers came from Nobel Laureate Kenneth G. Wilson's significant interests in Monte Carlo simulations of quantum field theories. The generality and usefulness of stochastic simulations has only begun to be explored and will lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Traditional normal RNGs are inefficient on vector processors. In 1993 the author compared various normal RNGs on vector processors and concluded that careful implementations of old methods such as the 1958 Polar method of Box, Muller and Marsaglia (see Knuth [21, Algorithm P]) and the 1959 Box-Muller method [21,28] were faster than more recent methods [22] on vector processors produced by companies such as Cray, Fujitsu, and NEC: see [8,30]. When Wallace's maximum-entropy idea appeared, it was clear that the landscape had changed, although the published implementation fastnorm was not intended to be efficient on vector processors.…”
Section: Maximum Entropy Normal Rngsmentioning
confidence: 99%
“…Traditional normal RNGs are inefficient on vector processors. In 1993 the author compared various normal RNGs on vector processors and concluded that careful implementations of old methods such as the 1958 Polar method of Box, Muller and Marsaglia (see Knuth [21, Algorithm P]) and the 1959 Box-Muller method [21,28] were faster than more recent methods [22] on vector processors produced by companies such as Cray, Fujitsu, and NEC: see [8,30]. When Wallace's maximum-entropy idea appeared, it was clear that the landscape had changed, although the published implementation fastnorm was not intended to be efficient on vector processors.…”
Section: Maximum Entropy Normal Rngsmentioning
confidence: 99%
“…In 1993 the author compared various normal RNGs on vector processors and concluded that careful implementations of old methods such as the 1958 Polar method of Box, Muller and Marsaglia (see Knuth [21,Algorithm P]) and the 1959 Box-Muller method [21,28] were faster than more recent methods [22] on vector processors produced by companies such as Cray, Fujitsu, and NEC: see [8,30]. When Wallace's maximum-entropy idea appeared, it was clear that the landscape had changed, although the published implementation fastnorm was not intended to be efficient on vector processors.…”
Section: Maximum Entropy Normal Rngsmentioning
confidence: 99%
“…We mention also the papers by Box and Muller (1958), Marsaglia and Bray (1964), Brent (1974), Eichenauer and Lehn (1986), Niederreiter (1988), Sugita (1995) and Antipov (1995Antipov ( , 1996. Random number generation on supercomputers was considered by Petersen (1988), Anderson (1990), Petersen (1994a) and Entacher, Uhl and Wegenkittl (1998).…”
Section: Euler Approximationmentioning
confidence: 99%